Profil Bakteri Patogen dan Antibiotik pada Gangren Diabetes Melitus di RSUD Abdul Wahab Sjahranie Samarinda - Desi Wahyuni; Suryanata Kesuma; Sresta Azahra (HEALTH CARE: JURNAL KESEHATAN, 2023)
Diabetes Mellitus can be triggered by environmental factors and unhealthy lifestyles such as overeating, fat, lack of activity, and stress. Diabetes Mellitus can also appear due to hereditary factors. Diabetes Mellitus can cause various complications including gangrenous wounds. To determine the appropriate use of antibiotics, appropriate treatment, and the spread of antibiotic resistance does not occur in patients with gangrene with Diabetes Mellitus, it is necessary to identify the appropriate bacterial species. The study aimed to identify the bacterial species found in wound infections in diabetic with gangrenous complications at AWS Hospital. This type of research is descriptive with exploratory design. The research sample was pus (pus) with gangrene in inpatient diabetic in November - December at AWS Hospital. A total of 29 samples were found in pus gangrenous DM wound infection, there were 11 species of gram-negative and gram-positive pathogenic bacteria. Antibiotic sensitivity test on the Staphylococcus epidermidis bacterial species was more resistant to antibiotics by 81%, the Proteus mirabilis bacterial species was more Intermediate against antibiotics by 65%, and the Proteus hauseri bacterial species was more sensitive to bacteria by 66%. The most infecting pathogenic bacteria are gram-negative bacteria with the species Proteus mirabilis and the most resistant and sensitive antibiotics are Ceftizoxime, gentamicin, and Piperacillin/Tazobactam.